Integrated Optimization of Service-Oriented Train Plan and Schedule on Intercity Rail Network with Varying Demand - Wenliang Zhou; Junli Tian; Lianbo Deng; Jin Qin (Discrete Dynamics in Nature and Society)
For a better service level of a train operating plan, we propose an integrated optimization method of train planning and train scheduling, which generally are optimized, respectively. Based on the cost analysis of both passengers travelling and enterprises operation, and the constraint analysis of trains operation, we construct a multiobjective function and build an integrated optimization model with the aim of reducing both passenger travel costs and enterprise operating costs. Then, a solving algorithm is established based on the simulated annealing algorithm. Finally, using as an example the Changzhutan intercity rail network, as an example we analyze the optimized results and the influence of the model parameters on the results.